Upaya Meningkatkan Motivasi Beserta Membangun Akhlak Karimah terhadap Masyarakat Desa Batu Gemuk Kecamatan Namorambe Kabupaten Deli Serdang - Hulu, Fajrimal; Andy, Safria; Dasopang, Masdeani; Lestari, Sri Dewi; Harahap, Septi Ayu (MODELING: Jurnal Program Studi PGMI, 2023)
Motivation plays a strategic role in individual activities. Every individual in their life has a motivation that drives them to achieve their desired goals. Losing motivation means losing direction and purpose in life. There are various methods that can be used to increase motivation, both through internal and external factors. One way to increase external motivation is by doing activities such as watching inspirational stories, reading motivational quotes, and so on. Issues of ethics or morality have consistently penetrated human life throughout the ages. Along with this journey of life, in each specific time period and location, individuals emerge who struggle to maintain moral values.